The temperature-dependent domains,SHG effect and piezoelectric coefficient of TGS - Xiong, Ren-Geng (Chinese chemical letters, 2013)
The temperature-dependent,second-order,nonlinear,optical coefficient（x~（（2）））.piezoelectric coefficient （d_（33））,pyroelectric coefficient（Ps） and domains on triglycine sulfate（TGS） reported herein provide a clue for us to investigate these as a typical second-order phase transition.The symmetry breaking occurrence is definitely confirmed by the temperature-dependent x~（（2）） in which x~（（2）） displays a limited value at the ferroelectric phase,indicating the space group（P2_1） chosen is correct,and when x~（（2）） basically maintains a zero value at the paraelectric phase,indicating the space group should be centric.Interestingly,after normalization of x~（（2））,d_（33） or Ps,the change trend with temperature is basically overlapped,probably abiding by Landau theory.Moreover,temperature-dependent domains directly show the symmetry breaking occurrence.